Progress in the balance : mythologies of development in Santos, Brazil - Reichman, Daniel R. (Daniel Ross), 1976- (Cornell University Press, 2023)
"A historical ethnography of the city of Santos, Brazil from 1900 to the present, which develops a new anthropological theory of progress"--